2018
DOI: 10.1159/000488593
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Smartphone-Based Testing of Interference in Parkinson’s Disease

Abstract: Background: Interference refers to learned associations and established behaviors “interfering” with response to new material. It forms a core pillar of executive functions, which are commonly affected in Parkinson’s disease (PD). Cognitive interference test (CIT) forms part of a smartphone application designed for ambulatory assessment in PD. Objective: The aims of this study were to establish that CIT could effectively demonstrate interference and would perform comparably to the Stroop Color-Word Test Victor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…However, this was not a validation study and its primary objective was to evaluate the usability and the compliance of a smartphone app for PD RPM. At the same time, it was possible to associate several quantified motor and cognitive outcomes to available disease severity indexes (disease duration, UPDRS-III total score, H&Y; Supplementary Materials), as also previously reported (10)(11)(12). Interestingly some of the motor and cognitive parameters-in particular TUG test datawere not associated to age but specific to the PD condition (Supplementary Table 3).…”
Section: Discussionmentioning
confidence: 75%
“…However, this was not a validation study and its primary objective was to evaluate the usability and the compliance of a smartphone app for PD RPM. At the same time, it was possible to associate several quantified motor and cognitive outcomes to available disease severity indexes (disease duration, UPDRS-III total score, H&Y; Supplementary Materials), as also previously reported (10)(11)(12). Interestingly some of the motor and cognitive parameters-in particular TUG test datawere not associated to age but specific to the PD condition (Supplementary Table 3).…”
Section: Discussionmentioning
confidence: 75%
“…During the COVID‐19 pandemic, in fact, the possibility of supporting patients with telerehabilitation protocols via mobile health, independent of their geographical location, could represent a positive opportunity, considering its accessibility and high motivational power based on the integration of playfulness and gamification 20–22 . Finally, mobile health is flexible, as its use is independent of time and place, and thus adaptable to the daily life of patients 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID‐19 pandemic, in fact, the possibility of supporting patients with telerehabilitation protocols via mobile health, independent of their geographical location, could represent a positive opportunity, considering its accessibility and high motivational power based on the integration of playfulness and gamification. 20 , 21 , 22 Finally, mobile health is flexible, as its use is independent of time and place, and thus adaptable to the daily life of patients. 23 , 24 It should be considered that previous studies have reported that patients who consider therapy to be useful and motivating show greater therapeutic adherence and involvement in therapy, especially in distant rehabilitation.…”
Section: Discussionmentioning
confidence: 99%